PERAN POLRI, KEJAKSAAN DAN MAHKAMAH ADAT ACEH DALAM PENEGAKAN SYARIAT ISLAM DI ACEH - Berutu, Ali Geno (IAIN Tulungagung, 2019)
The main institutions that play a very important role in the enforcement of Islamic law in Aceh are the Office of Islamic Law (DSI), the Shariah Court (MS) and Wilayatul Hisbah (WH) at the Aceh provincial level and the district level. The question proposed is what is the role of the national law enforcement agencies such as the Republic of Indonesia Police and the Republic of Indonesia Prosecutors' Office. As a matter of fact the application of Islamic law in Aceh is under the territory of the NKRI. It means that legally Aceh is not entirely independent but is still within the scope of national law enforcement. Therefore, the existence of the National Police and Prosecutors' Office in prosecuting its role in law enforcement in Aceh, particularly sharia-nuanced law is important to be investigated. This study uses a library approach of wihch primary sources are books, documents, laws, notes and online media about the implementation of Islamic law in this Veranda of Mecca.Keywords: Syariah Islam, Wilayatul Hisbah, MAA